A Pre-experimental Study to Assess the Effectiveness of Structured Teaching Plan about Knowledge Regarding Nosocomial Infection among Nurses in Selected Hospital - Salvi, Jayashree (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of the study was to assess the effectiveness of the structured teaching plan about knowledge regarding nosocomial infection among nurses in selected hospitals. Materials and Methods: A pre-experimental research study with one group pre-test post-test research design was conducted at K.J.Somaiya College of Nursing, Mumbai. The total population of the study was 30 nurses of K.J.Somaiya Hospital and Research Centre that were selected by non-probability sampling technique. Data were analyzed using descriptive and inferential statistics. Results: The result shows that demographic data of nurses, out of 30 samples maximum samples of 13 (43.2%) had area of experience to different specific area followed by 7 (23.4%) samples had area of experience of surgical ward whereas, 5samples (16.7%) had area of experience of medical ward and ICU. The result related to demographic data showed that out of total subjects maximum sample about 26 (66.6%) were found to be registered staff nurses, followed by 2 (6.7%) samples worked as senior staff nurses and 02 (6.9%) were at other post. Major findings showed that pre-test knowledge score was 40% and mean was 14 whereas, post-test knowledge score was 60% and mean was 15. The comparison of pre-test knowledge score was found 40% and mean was 14 while the post-test score was 60% and mean was 15. Conclusion: The study observed that the nurses did not have adequate knowledge about nosocomial infection and the knowledge and practices need to be improved so as to prevent nosocomial infection.